2016
DOI: 10.1007/s11596-016-1628-1
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan reduced cerebral edema by inhibiting NLRP3 inflammasome in mice with cold brain injury

Abstract: The aim of this study was to investigate the possible beneficial role of telmisartan in cerebral edema after traumatic brain injury (TBI) and the potential mechanisms related to the nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) pyrin domain-containing 3 (NLRP3) inflammasome activation. TBI model was established by cold-induced brain injury. Male C57BL/6 mice were randomly assigned into 3, 6, 12, 24, 48 and 72 h survival groups to investigate cerebral edema development with time and receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The few papers, so far published on the role of NLRP3 in TBI used indirect strategies to prevent NLRP3 activation (Liu et al, 2013; Dong et al, 2016; Ma et al, 2016; Wei et al, 2016; Lin et al, 2017). A study using telmisartan in mice subjected to cold brain injury showed that the treatment reduced oxidative stress and brain oedema, as a consequence NLRP3 and IL-1b production were decreased; however, the effect on this pathway is rather indirect than direct (Wei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few papers, so far published on the role of NLRP3 in TBI used indirect strategies to prevent NLRP3 activation (Liu et al, 2013; Dong et al, 2016; Ma et al, 2016; Wei et al, 2016; Lin et al, 2017). A study using telmisartan in mice subjected to cold brain injury showed that the treatment reduced oxidative stress and brain oedema, as a consequence NLRP3 and IL-1b production were decreased; however, the effect on this pathway is rather indirect than direct (Wei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A study using telmisartan in mice subjected to cold brain injury showed that the treatment reduced oxidative stress and brain oedema, as a consequence NLRP3 and IL-1b production were decreased; however, the effect on this pathway is rather indirect than direct (Wei et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of recent studies have found that pharmacological treatments that directly or indirectly target this inflammasome can reduce its activity following moderate-to-severe TBI. These treatments are broadly broken into four groups: (i) treatments derived from naturally occurring compounds (e.g., mangiferin [83], omega-3 fatty acids [71], and apocynin [84]); (ii) repurposed medications (e.g., propofol [85], and telmisartan [86]); (iii) inhibitors of NLRP3-associated molecules (e.g., ASC antibodies [87], NF-κB inhibitor, Bay 11-7082 [88][89][90][91]); and (iv) specific NLRP3 inflammasome inhibitors (e.g., MCC950 [69], JC-124 [92]). While the first three treatment categories have been shown to decrease NLRP3 inflammasome activity as well as demonstrating a neuroprotective effect, they do not target NLRP3 activation specifically.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
“…Neurobehavioral assessment was performed at 24 and 72 h post-TBI in a blinded fashion using a 10-point neurological severity score (NSS). 18 One point was given for each failure to account for the cumulative score with a maximum of 10. The assessment consisted of 10 different tasks: 1) presence of mono-or hemiparesis; 2) inability to walk on a 3-cm-wide beam; 3) inability to walk on a 2-cm-wide beam; 4) inability to walk on a 1-cm-wide beam; 5) inability to balance on a 1-cm-wide beam; 6) inability to balance on a round stick (0.5 cm diameter); 7) failure to exit a 30-cm-diameter circle (for 2 min); 8) inability to walk a straight line; 9) loss of startle behavior; and 10) loss of seeking behavior.…”
Section: Assessment Of Neurological Severity Scorementioning
confidence: 99%
“…Applying general neuroprotectives like omega-3 fatty acids or telmisartan in experimental TBI, there are some earlier studies to suggest the association with NLRP3 inhibition may account for the therapeutic effects. 16,18,19 Nevertheless, generally acting as antioxidants or peleiotropic agents, the implication of a wide array of effectors may not be ruled out for such multipotential compounds. 20,21 Based on such a background, we used the newly developed NLRP3 inhibitor, MCC950, as a highly selective and potent inhibitor, to specify the involvement of NLRP3.…”
Section: Introductionmentioning
confidence: 99%